Penguatan Literasi Digital sebagai Sarana Pengembangan Skill Pemrograman bagi Masyarakat Umum - Dion Winarno; Idham Khalik (UNITY: Journal of Community Service, 2025)
Programming skills have become essential competencies in adapting to the digital era, especially for urban communities seeking to engage with the rapid advancement of information technology. This community service program aimed to strengthen digital literacy as a foundation for developing basic programming skills among the general public in Teluk Pucung, North Bekasi. The methods employed included awareness sessions, interactive training, and guided practice using accessible online learning platforms. The program targeted productive-age participants with an interest in technology but limited prior exposure to digital literacy or programming. The results indicated a significant improvement in participants’ understanding of fundamental digital concepts and basic programming skills, particularly in algorithmic thinking and introductory Python programming. Furthermore, the participants demonstrated high enthusiasm and motivation to pursue further independent learning. This initiative contributed meaningfully to promoting inclusive access to technology education and empowering communities to meet future digital challenges.